Permasalahan Pendidikan dalam Kajian Filsafat Pendidikan Islam - Hasanah, Fadilatul; Ramadhan, Firman Aulia; Wahono, Suparwoto Sapto; Machfudi, Moch Imam (IJIT: Indonesian Journal of Islamic Teaching, 2025)
This paper aims to examine various issues that arise in discussing the philosophy of Islamic education. This paper will examine educational issues in the aspects of ontology, epistemology, and axiology. The ontological issues of education in the study of Islamic educational philosophy are divided into three issues: Islamic education, which seeks guidance, education, and coaching in introducing Islam as a whole to students; Faith education, which seeks the totality of Islamic teachings to be instilled in children through faith in Allah SWT with the foundations of faith, the pillars of Islam, and the foundations of sharia; and Ihsan education, which instills confidence in the mood and behavior of students to always feel close to God so that their actions are in accordance with the rules of Allah SWT. The epistemological issue of education in the study of Islamic educational philosophy is the educational process within the Islamic educational system, the scope of which is the objectives of Islamic education, the curriculum of Islamic education, Islamic educational materials, Islamic educational methods, educators, students, Islamic educational facilities, Islamic educational tools, and Islamic educational approaches. The problem of educational axiology in the study of Islamic educational philosophy concerns the values of Islamic education itself with the aim of testing and integrating all these values in human life, maintaining and fostering them in their personalities, both spiritual and tangible, which are divided into two main values, namely divine values and human values. Keyword: Educational Issues, Philosophy, Islamic Education.